EVALUASI BOS REGULER DALAM PENINGKATAN MUTU PENDIDIKAN DI SEKOLAH TK DARUL ULUM DOYO BARU JAYAPURA, PAPUA - Farida, Nurul; Sigalingging, Berlian Novalita; Destiyani, Gati; Resdianto, Andreas; Ismanto, Bambang; Rambu, Apriani Dorkas (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research examines how well TK Darul Ulum Doyo Baru utilized BOS in Stage 1 of 2024 in Jayapura, Papua, and how efficiently they were used. The BOS program aims to provide free basic education to students, improve their education, and reduce financial pressure. This research uses a descriptive qualitative approach because the data is derived from interviews and written records. The study found that the school has effectively utilized the BOS by adhering to all relevant rules and technical guidelines. Among the various uses of the BOS are curriculum development, procurement of educational playground equipment, coordination of nutrition programs, and payment of teacher honorariums. Signs of success include increased enrollment, better classroom management, and an overall increase in trust towards the school. According to this research, effective management and collaboration are crucial for schools and foundations to ensure that their funds are usedwisely.